Sufficient application of NPK fertilizers: A practical and efficient strategy in the management of Verticillium wilt of potato var. Agria - Akbar Hemmati; Bahram Mansoori (Journal of Crop Protection, 2016)
Field experiment was conducted in 2010 and 2011, in order to study the effects of NPK fertilizers on the incidence of Verticillium wilt of a commercial variety 'Agria' in deficient soil at Eghlid Agriculture Research Station in the north of Fars province, Iran. Experimental design was randomized complete blocks and each treatment replicated three times. Treatments were the amounts of recommended NPK rate (180N, 125P, 100K), 20% and 40 % less and more than the rate based on the soil tests. Soil at planting sites was inoculated with 5 ml of microsclerotia suspension (70 ms/ml). Tubers weight, plant height and disease scores were recorded. Two-year combined analysis indicated that there were significant differences at 1% level between the treatments. The results showed a marked decrease in Verticillium wilt incidence and increase in yield when NPK was used at the recommended rate. Lowest disease score and highest yield even more than the cultivar potential were obtained in the plots when N was used 40 % more than the recommended level of the soil test (252 N), combined with K at the level of the soil test (100 K). P was essential for plant growth but had no effect on the disease.